Diagnostic Accuracy of Wells Score and PERC Score to Predict Pulmonary Embolism in Suspected Cases - Siddique, Izza; Ahmad, Jamal; Rafique, Zahra; Iqbal, Hina; Rafaqat, Mishal; Mushtaq, Ghazal (Biological and Clinical Sciences Research Journal, 2025)
Pulmonary embolism (PE) is a potentially life-threatening condition requiring prompt and accurate diagnosis. Clinical decision rules such as the Wells score and the Pulmonary Embolism Rule-out Criteria (PERC) are widely used to estimate pretest probability and reduce unnecessary imaging. However, their diagnostic performance remains variable across populations. Objective: To determine the diagnostic accuracy of the Wells score and PERC criteria in predicting pulmonary embolism, using computed tomography pulmonary angiography (CTPA) as the gold standard, in suspected cases. Methods: This validation study was conducted at the Pulmonology Unit of Fauji Foundation Hospital, Rawalpindi. One hundred ninety-eight patients presenting with clinical suspicion of PE were enrolled consecutively between 18 October 2024 and 19 February 2025. In all patients, the senior registrar on duty calculated the Wells and PERC scores before CTPA was performed. The final diagnosis of PE was confirmed through CTPA. Statistical analysis included calculation of sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy (DA). Results: The mean age of the participants was 56 ± 8 years. The Wells score demonstrated a sensitivity of 62.4%, specificity of 63.0%, PPV of 70.9%, NPV of 53.7%, and DA of 62.6%. The PERC criteria showed a higher sensitivity of 75.2%, but a lower specificity of 38.2%, with PPV at 63.8%, NPV at 51.7%, and DA at 60%. Conclusion: The Wells and PERC scores exhibited limited diagnostic accuracy in predicting pulmonary embolism compared to CTPA. These clinical assessment tools, therefore, cannot reliably exclude PE or sufficiently reduce the need for confirmatory imaging in the pulmonary emergency setting.